What goes around comes around. Supply and demand side of climate change at the example of Norway - Pieńkowski, Dariusz (Frontiers in Energy Research, 2025)
Norway is widely acknowledged as an environmentally advanced economy, with a significant proportion of renewable energy resources. Nevertheless, it is evident that Norway’s economic achievements and capacity to invest in sustainable energy resources have been largely supported by its trade in non-renewable resources. The utilisation of these resources has been associated with the emission of greenhouse gases, which has considerable ramifications for climate change and is also contributing to the melting of Norwegian glaciers. The objective of this research is to examine the issue of moral responsibility and the socio-economic costs associated with the management of natural resources, as well as the socio-economic impacts on a global scale. It is observed that actions intended to yield immediate and localised benefits may, in fact, result in adverse outcomes for those responsible for their implementation. The responsibility on the supply side is not only determined by moral considerations, but also by the socio-economic consequences that can be quantified for the perpetrators. Norway provides an illustrative example of the challenges posed by the consequences of glacial melting, which introduce additional risks and challenges to the use of hydropower. The loss of these resources is comparable to the destruction of tropical forests and has significant consequences, as they are considered the green lungs of the world and a reservoir of biodiversity.